Analysis of the Impact of Work Discipline and Motivation on Employee Performance PT. Presisi Housing Development Cilegon - Cahyani, Shelli; Dinar Nur Affini; C. Catur Widayati (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to analyze the effect of work discipline and work motivation on employee performance. The population in this study was 52 employees of PT company development Precision Cilegon. The sample used was 52 employees. Sampling method using saturated sampling. The data collection method uses a survey method, with the research instrument being a questionnaire. The data analysis method uses the Statistical Package for the Social Sciences. This study proves that work discipline has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance